Long-term CO 2-enrichment in a Mediterranean natural forest: An application of large Open Top Chambers - Angelis, P De; Scarascia-Mugnozza, G E (Chemosphere, 1998)
It is crucial to be able to anticipate the possible effects of environmental changes on the Mediterranean woodland communities given their essential role on protecting lands that are under a strong pressure by man and climate. Predictions of the effects of increasing C0~ concentration on plants have been inferred by short- and long-term studies, conducted at different scales and by different technologies. Open Top Chambers (OTCs) are experimental facilities that have been widely used to expose field grown plants to different pollutant gases, and more recently to elevated [CO2] . In this paper, we present the natural site and the experimental system (six large OTCs enclosing clumps of natural vegetation) that we have been utilizing for 3 years, to assess the impact of elevated [CO2] on a Mediterranean natural forest community. The results show that large OTCs can be usefully used to simulate C02 doubling even under the harsh environmental conditions of the mediteffanean region
Keywords: decomposition; Elevated CO3; leaf litter; Mediterranean forest (voyant)

Long-term CO 2-enrichment in a Mediterranean natural forest: An application of large Open Top Chambers - Angelis, P. De; Scarascia-Mugnozza, G. E. (Chemosphere, 1998)
It is crucial to be able to anticipate the possible effects of environmental changes on the Mediterranean woodland communities given their essential role on protecting lands that are under a strong pressure by man and climate. Predictions of the effects of increasing C0~ concentration on plants have been inferred by short- and long-term studies, conducted at different scales and by different technologies. Open Top Chambers (OTCs) are experimental facilities that have been widely used to expose field grown plants to different pollutant gases, and more recently to elevated [CO2] . In this paper, we present the natural site and the experimental system (six large OTCs enclosing clumps of natural vegetation) that we have been utilizing for 3 years, to assess the impact of elevated [CO2] on a Mediterranean natural forest community. The results show that large OTCs can be usefully used to simulate C02 doubling even under the harsh environmental conditions of the mediteffanean region
Keywords: decomposition; Elevated CO3; leaf litter; Mediterranean forest (voyant)